2018
DOI: 10.1111/bju.14191
|View full text |Cite
|
Sign up to set email alerts
|

Reproductive organ‐sparing cystectomy significantly improves continence in women after orthotopic bladder substitution without affecting oncological outcome

Abstract: Superior continence rates were found for ROSC with an OBS compared with SC, without a negative impact on oncological outcome. ROSC should, therefore, be offered to women receiving an OBS whenever justifiable.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 22 publications
0
4
0
Order By: Relevance
“…Finley et al [ 13 ] emphasized that pseudocystocele and urethral kinking are anatomical changes associated with urinary retention after orthotopic bladder substitution. Sparing of the gynecologic organs, such as the round ligament, during radical cystectomy may play a role in continence [ 17 18 ]; however, further prospective comparative studies are needed. Ali-el-Dein et al [ 14 ] reported a low rate of urethral recurrence after radical cystectomy following orthotopic bladder substitution, suggesting the continued use of this type of diversion.…”
Section: Discussionmentioning
confidence: 99%
“…Finley et al [ 13 ] emphasized that pseudocystocele and urethral kinking are anatomical changes associated with urinary retention after orthotopic bladder substitution. Sparing of the gynecologic organs, such as the round ligament, during radical cystectomy may play a role in continence [ 17 18 ]; however, further prospective comparative studies are needed. Ali-el-Dein et al [ 14 ] reported a low rate of urethral recurrence after radical cystectomy following orthotopic bladder substitution, suggesting the continued use of this type of diversion.…”
Section: Discussionmentioning
confidence: 99%
“…Research in the field of genital-sparing cystectomy (GSC) techniques to improve functional outcomes after cystectomy is gaining prominence [50] . Gross et al [51] and Wishahi et al [52] recently investigated the impact of GSC and subsequent ONB compared with standard RC in maintaining functional outcomes such as urinary continence in women.…”
Section: Discussionmentioning
confidence: 99%
“…The latter showed that GSC with ONB led to a minimal incidence of hypercontinence (7.80%), while standard RC led to a higher incidence (28.88%) [52] . A recent systematic review of the literature regarding OSC techniques showed that preservation of the genital or pelvic organs, in both men and women, yields better sexual outcomes than standard RC without compromising oncologic outcomes; however, the authors emphasized that none of these techniques could be recommended as superior to standard RC, and that large-scale prospective and multi-institutional studies are needed to identify patients suitable for these techniques [50] .…”
Section: Discussionmentioning
confidence: 99%
“…After a constant rise in the number of orthotopic bladder substitution procedures since their introduction in the mid 80s, a plateau was reached at the beginning of this century when nearly 50% of all urinary diversion surgeries performed in high-volume centres worldwide involved © 2020 The Authors BJU International © 2020 BJU International 655 orthotopic bladder substitution [23]. Initially reserved for men, female orthotopic bladder reconstruction was later implemented in clinical routine, with excellent voiding and storage function outcomes in selected patients, especially after widespread utilization of reproductive organ-sparing cystectomy, and therefore became the preferable form of CUD for both sexes [24][25][26]. In the following years, the number of orthotopic bladder substitution surgeries decreased as a result of unsatisfactory results obtained by inexperienced surgeons and the introduction of minimally invasive surgery, in which the orthotopic bladder substitute configuration is a challenge [27].…”
Section: Orthotopic Bladder Substitutionmentioning
confidence: 99%